All-solid-state batteries
Patent Information
- Application Number
- JP2024502807
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-28
- Filing Date
- 2022-09-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-09-28
AI Technical Summary
【0015】 上記態様にかかる全固体電池は、内部抵抗が低い。
Smart Images

Figure 0007933858000005 
Figure 0007933858000006 
Figure 0007933858000007
Abstract
Description
[Technical Field]
[0001] This invention relates to an all-solid-state battery. This application claims priority under Japanese Patent Application No. 2022-029457, filed in Japan on February 28, 2022, the contents of which are incorporated herein by reference. [Background technology]
[0002] In recent years, advancements in electronics technology have been remarkable, leading to the miniaturization, weight reduction, thinning, and increased functionality of portable electronic devices. Consequently, there is a strong demand for smaller, lighter, thinner batteries, and improved reliability for the batteries that power these devices, and all-solid-state batteries, which use solid electrolytes, are attracting attention.
[0003] Solid-state batteries come in two types: thin-film and bulk. Thin-film batteries are manufactured using thin-film technologies such as physical vapor deposition (PVD) and sol-gel methods. Bulk batteries are manufactured using methods such as powder molding and sintering. Each type of solid-state battery has different materials that can be used and therefore different performance characteristics due to the differences in manufacturing methods. For example, bulk batteries using sintered bodies require materials that can withstand sintering, but they can achieve high capacity because each layer can be made thicker.
[0004] For example, Patent Document 1 discloses a sintered all-solid-state battery using an oxide-based solid electrolyte. The all-solid-state battery described in Patent Document 1 presents several materials applicable to the positive electrode active material layer and the solid electrolyte layer. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] International Publication No. 2007 / 135790 [Overview of the project] [Problems that the invention aims to solve]
[0006] Some of the all-solid-state batteries described in Patent Document 1 had high internal resistance.
[0007] This invention has been made in view of the above problems, and aims to provide an all-solid-state battery with low internal resistance. [Means for solving the problem]
[0008] To solve the above problems, the following means are provided.
[0009] (1) The all-solid-state battery according to the first embodiment comprises a sintered body. The sintered body has a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode. The positive electrode contains a compound having a spinel structure. The solid electrolyte layer contains a solid electrolyte having a γ-Li3PO4 type crystal structure. The compound having a spinel structure is Li α M β Mn 2-β It is represented by O4···(1). In equation (1) above, M is one or more atoms selected from transition metals, satisfying 0.8≦α≦1.2 and 0.1≦β≦0.9.
[0010] (2) In the all-solid-state battery according to the above embodiment, M may be Ni. Formula (1) is Li α Ni β Mn 2-β It can be expressed as O4···(2) and satisfies 0.4≦β≦0.6.
[0011] (3) In the all-solid-state battery according to the above embodiment, the positive electrode may further contain Ag or an Ag alloy.
[0012] (4) In the all-solid-state battery according to the above embodiment, the positive electrode may comprise a first layer and a second layer. The first layer comprises the compound and Ag or an Ag alloy, and the second layer is in contact with at least one main surface of the first layer.
[0013] (5) In the all-solid-state battery according to the above embodiment, the volume ratio of Ag and Ag alloy in the first layer may be 40% or more and 85% or less.
[0014] (6) In the all-solid-state battery according to the above aspect, the solid electrolyte contained in the solid electrolyte layer may be Li 3+x Si x P 1-x O4 (0.2≦x≦0.6).
Effects of the Invention
[0015] The all-solid-state battery according to the above aspect has low internal resistance.
Brief Description of the Drawings
[0016] [Figure 1] It is a cross-sectional view of the all-solid-state battery according to the first embodiment. [Figure 2] It is an enlarged cross-sectional view of the characteristic portion of the all-solid-state battery according to the first embodiment. [Figure 3] It is an enlarged cross-sectional view of the characteristic portion of another example of the all-solid-state battery according to the first embodiment. [Figure 4] It is an enlarged cross-sectional view of the characteristic portion of the positive electrode of another example of the all-solid-state battery according to the first embodiment. [Figure 5] It is an enlarged cross-sectional view of the characteristic portion of the positive electrode of another example of the all-solid-state battery according to the first embodiment. [Figure 6] It is an enlarged cross-sectional view of the characteristic portion of another example of the all-solid-state battery according to the first embodiment.
Modes for Carrying Out the Invention
[0017] Hereinafter, the present embodiment will be described in detail with appropriate reference to the drawings. The drawings used in the following description may in some cases show characteristic portions enlarged for convenience in order to make the features of the present invention easier to understand, and the dimensional ratios and the like of each component may differ from the actual ones. The materials, dimensions, and the like illustrated in the following description are merely examples, and the present invention is not limited thereto, and can be implemented with appropriate modifications without departing from the gist thereof.
[0018] The directions are defined as follows: The stacking direction of the laminate 4 is defined as the z-direction, one direction in the plane perpendicular to the z-direction is defined as the x-direction, and the direction perpendicular to both the x-direction and the z-direction is defined as the y-direction. Hereafter, one direction in the z-direction may be referred to as "up," and the opposite direction may be referred to as "down." Up and down do not necessarily coincide with the direction in which gravity acts.
[0019] Figure 1 is a schematic cross-sectional view of an all-solid-state battery 10 according to this embodiment. The all-solid-state battery 10 has a laminate 4 and terminal electrodes 5 and 6. The terminal electrodes 5 and 6 are in contact with opposing surfaces of the laminate 4, respectively. The terminal electrodes 5 and 6 extend in the z direction, which intersects (is perpendicular to) the laminate surface of the laminate 4.
[0020] The laminate 4 has a positive electrode 1, a negative electrode 2, and a solid electrolyte layer 3. The laminate 4 is a sintered body formed by laminating and sintering the positive electrode 1, the negative electrode 2, and the solid electrolyte layer 3. The number of layers for the positive electrode 1 and the negative electrode 2 is not limited. The solid electrolyte layer 3 is located at least between the positive electrode 1 and the negative electrode 2. Between the positive electrode 1 and the terminal electrode 6, and between the negative electrode 2 and the terminal electrode 5, there is, for example, the same solid electrolyte as the solid electrolyte layer 3. One end of the positive electrode 1 is connected to the terminal electrode 5. One end of the negative electrode 2 is connected to the terminal electrode 6.
[0021] The all-solid-state battery 10 charges or discharges by the exchange of ions between the positive electrode 1 and the negative electrode 2 via the solid electrolyte layer 3. The all-solid-state battery 10 shown in Figure 1 is a stacked type battery, but the all-solid-state battery 10 may also be a wound type battery. The all-solid-state battery 10 is used in laminate batteries, prismatic batteries, cylindrical batteries, coin type batteries, button type batteries, etc. The all-solid-state battery 10 may also be a liquid-injection type in which the solid electrolyte layer 3 is dissolved or dispersed in a solvent.
[0022] "Positive electrode" Figure 2 is an enlarged view of a characteristic part of the all-solid-state battery 10 according to the first embodiment. The positive electrode 1 has, for example, a positive electrode current collector layer 1A and a positive electrode active material layer 1B. The positive electrode current collector layer 1A is an example of a first layer, and the positive electrode active material layer 1B is an example of a second layer. The second layer is in contact with at least one main surface of the first layer. The positive electrode 1 contains a compound having a spinel structure that satisfies formula (1), which will be described later. The positive electrode 1 may further contain Ag or an Ag alloy.
[0023] [Positive electrode current collector layer] The positive electrode current collector layer 1A includes, for example, a positive electrode current collector 11 and a positive electrode active material 12. In this case, the area between the xy plane passing through the top and the xy plane passing through the bottom of the positive electrode current collector 11 is considered to be the positive electrode current collector layer 1A.
[0024] The positive electrode current collector 11 consists of a plurality of current collector particles. The plurality of current collector particles are connected to each other and electrically connected in the xy plane. The positive electrode current collector layer 1A comprises a metal or alloy containing one or more selected from the group consisting of, for example, Ag, Pd, Au, and Pt. These metals or alloys do not melt and are not easily oxidized even when the laminate 4 is heated in an atmospheric environment. The positive electrode current collector layer 1A preferably contains Ag or an Ag alloy. The positive electrode current collector 11 is, for example, an AgPd alloy, Au, Pt, or a mixture thereof. The composition ratio of each component of the alloy is not specified.
[0025] The total volume ratio (Va) of Ag and Ag alloy in the positive electrode current collector layer 1A is, for example, between 40% and 85%. The volume ratio is approximately equal to the area ratio in a cross-section measured by a scanning electron microscope. Therefore, the area ratio in a cross-section measured by a scanning electron microscope can be directly considered as the volume ratio. Ag and Ag alloy can be distinguished from the contrast of images obtained using a scanning electron microscope. Furthermore, to extract only the volume ratio of Ag from Ag and Ag alloy, the composition ratio can be quantitatively analyzed using energy-dispersive X-ray spectroscopy (EDS), and the volume ratio of Ag can be determined by calculating the product of that ratio and the volume ratio of Ag and Ag alloy.
[0026] The positive electrode active material 12 is mixed together with the positive electrode current collector 11 in the positive electrode current collector layer 1A. The positive electrode active material 12 is in contact with the positive electrode current collector 11. When the positive electrode active material 12 is contained in the positive electrode current collector layer 1A, the transfer of lithium ions within the positive electrode current collector layer 1A becomes smoother. The positive electrode 1 contains a compound having a spinel structure as the positive electrode active material 12. The compound having a spinel structure is Li α M β Mn 2-β It is represented as O4···(1).
[0027] In formula (1), M is one or more atoms selected from transition metals. In formula (1), M is, for example, one or more atoms selected from the group consisting of Ni, Co, and Ti. In formula (1), M is, for example, Ni. If M in formula (1) is Ni, then formula (1) is Li α Ni β Mn 2-β It is represented as O4···(2).
[0028] In equations (1) and (2), α satisfies 0.8 ≤ α ≤ 1.2. In equations (1) and (2), β satisfies 0.1 ≤ β ≤ 0.9, preferably 0.4 ≤ β ≤ 0.6.
[0029] The compound represented by formula (1) is, for example, LiNi 0.1 Mn 1.9 O4, LiSa 0.5 Mn 1.5 O4, LiSa 0.9 Mn 1.1 O4, LiCo 0.1 Mn 1.9 O4, LiCo 0.5 Mn 1.5 O4, LiCo 0.9 Mn 1.1 O4, LiTi 0.1 Mn 1.9 O4, LiTi 0.5 Mn 1.5 O4, LiTi 0.9 Mn 1.1 It is O4.
[0030] The positive electrode active material 12 may include a transition metal oxide containing one or more elements selected from the group consisting of Co, Ni, Mn, Fe, and V, in addition to the spinel structure compound represented by formula (1). For example, the positive electrode active material 12 may contain a spinel structure LiNi 0.5 Mn 1.5 It may also contain O4 and LiMn2O4.
[0031] Figure 2 shows an example in which the positive electrode current collector 11 consists of multiple current collector particles, but is not limited to this case. Figure 3 is an enlarged view of a characteristic part of another example of an all-solid-state battery according to the first embodiment. The positive electrode current collector layer 1C shown in Figure 3 consists of foil-like positive electrode current collectors 11 that spread in the xy plane. The positive electrode current collectors 11 may also be in the form of a punched film or an expanded film that spreads in the xy plane. The positive electrode current collector layer 1C may consist of positive electrode current collectors 11.
[0032] [Cathode active material layer] The positive electrode active material layer 1B is formed on one or both sides of the positive electrode current collector layer 1A. The positive electrode active material layer 1B contains positive electrode active material. The positive electrode active material layer 1B may also contain a conductive additive, a binder, and the solid electrolyte described above. If the positive electrode active material layer 1B contains a solid electrolyte, the xy plane passing through the outermost part of the positive electrode active material is considered to be the boundary between the positive electrode active material layer 1B and the solid electrolyte layer 3.
[0033] (Cathode active material) The positive electrode active material includes a compound with a spinel structure represented by formula (1). In addition to the compound with a spinel structure represented by formula (1), the positive electrode active material 12 may also include a transition metal oxide containing one or more selected from the group consisting of Co, Ni, Mn, Fe, and V. For example, the positive electrode active material 12 may be a LiNi compound with a spinel structure. 0.5 Mn 1.5 It may also contain O4 and LiMn2O4.
[0034] (Conductive additive) The conductive additive is not particularly limited as long as it improves the electronic conductivity within the positive electrode active material layer 1B, and known conductive additives can be used. Examples of conductive additives include carbon-based materials such as graphite, carbon black, graphene, and carbon nanotubes, metals such as gold, platinum, silver, palladium, aluminum, copper, nickel, stainless steel, and iron, conductive oxides such as ITO, or mixtures thereof. The conductive additive may be in powder or fibrous form.
[0035] (Binding agent) The binder joins the positive electrode current collector layer 1A to the positive electrode active material layer 1B, the positive electrode active material layer 1B to the solid electrolyte layer 3, and the various materials that make up the positive electrode active material layer 1B to each other.
[0036] The binder can be used within a range that does not impair the function of the positive electrode active material layer 1B. The binder may be omitted if it is not needed. The binder content in the positive electrode active material layer 1B is, for example, 0.5 volume% to 30 volume% of the positive electrode active material layer. If the binder content is sufficiently low, the resistance of the positive electrode active material layer 1B will be sufficiently low. Here, the volume% is approximately equal to the area% of the cross-section measured by a scanning electron microscope, for example. Therefore, the area ratio of the cross-section measured by a scanning electron microscope can be directly considered as the volume ratio.
[0037] The binder can be any material capable of the above-mentioned bonding, such as fluororesins like polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). In addition to the above, other binders such as cellulose, styrene-butadiene rubber, ethylene-propylene rubber, polyimide resin, and polyamide-imide resin may also be used. Furthermore, conductive polymers with electronic conductivity or ionic conductive polymers with ionic conductivity may be used as binders. Examples of conductive polymers with electronic conductivity include polyacetylene. In this case, the binder also functions as a conductive additive, so it is not necessary to add a conductive additive. Examples of ionic conductive polymers with ionic conductivity include those that conduct lithium ions, such as monomers of polymer compounds (polyether-based polymer compounds such as polyethylene oxide and polypropylene oxide, polyphosphozenes, etc.) and lithium salts such as LiClO4, LiBF4, LiPF6, or alkali metal salts mainly composed of lithium. Polymerization initiators used in compounding include, for example, photopolymerization initiators or thermal polymerization initiators compatible with the above-mentioned monomers. Required properties for the binder include oxidation / reduction resistance and good adhesion.
[0038] Up to this point, specific examples of positive electrodes have been shown, but positive electrodes are not limited to these examples. For example, the positive electrode may be a single layer in which the positive electrode current collector 11 and the positive electrode active material 12 are mixed. Also, for example, Figures 4 and 5 are cross-sectional views of another example of a positive electrode according to the first embodiment.
[0039] The positive electrode shown in Figure 4 has a positive electrode current collector layer 1D and a positive electrode active material layer 1B. The positive electrode current collector layer 1D has a positive electrode current collector 11, a positive electrode active material 12, and an oxide 13. The oxide 13 is, for example, an oxide containing Ag, such as AgCoO2 or AgMn2O4. The oxide 13 contains, for example, the constituent elements of the positive electrode current collector 11 and the constituent elements of the positive electrode active material 12. The oxide 13 prevents the oxidation of Ag contained in the positive electrode current collector 11. The presence of the oxide 13 between the positive electrode current collector 11 and the positive electrode active material 12 improves the cycle characteristics of the all-solid-state battery 10.
[0040] The positive electrode shown in Figure 5 has a positive electrode current collector layer 1E, an intermediate layer 1F, and a positive electrode active material layer 1B. The positive electrode current collector layer 1E has a positive electrode current collector 11 and an oxide 13. The intermediate layer 1F consists of the oxide 13. The example shown in Figure 5 corresponds to the case where the thickness of the oxide 13 is thicker than the example shown in Figure 4. The oxide 13 prevents oxidation of Ag contained in the positive electrode current collector 11, improving the cycle characteristics of the all-solid-state battery 10.
[0041] "Solid electrolyte layer" The solid electrolyte layer 3 contains a solid electrolyte. The solid electrolyte is a material that can move ions by an externally applied electric field. For example, the solid electrolyte layer 3 conducts lithium ions and inhibits electron movement. The solid electrolyte layer 3 is, for example, a sintered body obtained by sintering.
[0042] The solid electrolyte layer 3 includes, for example, a solid electrolyte having a γ-Li3PO4 type crystal structure. Solid electrolytes having a γ-Li3PO4 type crystal structure have excellent ionic conductivity. The solid electrolyte is, for example, Li 3+x Si x P 1-x O4, Li 3+x Si x V 1-x O4, Li 3+x Ge x P 1-x O4, Li 3+x Ge x V 1-x It is O4, preferably Li 3+x Si x P 1-x The electrolyte is O4. x satisfies 0.4 ≤ x ≤ 0.8, preferably 0.2 ≤ x ≤ 0.6. The solid electrolyte may also be a ternary lithium oxide containing Si, V, and Ge, etc.
[0043] "Negative electrode" The negative electrode 2 includes, for example, a negative electrode current collector layer 2A and a negative electrode active material layer 2B containing a negative electrode active material.
[0044] [Negative electrode current collector] The negative electrode current collector layer 2A includes, for example, a negative electrode current collector 21 and a negative electrode active material 22. In this case, the negative electrode current collector layer 2A is considered to be the area between the xy plane passing through the top and the xy plane passing through the bottom of the negative electrode current collector 21.
[0045] The negative electrode current collector 21 comprises a metal or alloy containing, for example, one selected from the group consisting of Ag, Pd, Au, and Pt. Examples of negative electrode current collectors 21 include Ag, AgPd alloy, Li-Ag alloy, and mixtures thereof. The negative electrode current collector 21 may be the same as or different from the positive electrode current collector 11. The negative electrode current collector 21 also functions as a negative electrode active material.
[0046] As shown in Figure 3, the negative electrode current collector layer 2C may consist of a negative electrode current collector 21. In this case, the negative electrode current collector 21 may be a foil extending in the xy plane, or it may be in the form of punching or expanding.
[0047] [Negative electrode active material layer] The negative electrode active material layer 2B is formed on one or both sides of the negative electrode current collector layer 2A. The negative electrode active material layer 2B contains negative electrode active material. The negative electrode active material layer 2B may also contain a conductive additive, a binder, and the solid electrolyte described above. If the negative electrode active material layer 2B contains a solid electrolyte, the area between the xy plane passing through the top and the xy plane passing through the bottom of the negative electrode active material is considered to be the negative electrode active material layer 2B.
[0048] (Negative electrode active material) The negative electrode active material is a compound capable of intercalating and releasing ions. The negative electrode active material is a compound exhibiting a lower potential than the positive electrode active material. An example of a negative electrode active material is Li4Ti5O 12 It includes LiTiO2, Li2TiO3, and Li2TiSiO5. The negative electrode active material may contain multiple active material materials.
[0049] (Conductive additive) The conductive additive improves the electronic conductivity of the negative electrode active material layer 2B. The conductive additive can be made from the same material as that used for the positive electrode active material layer 1B.
[0050] (Binding agent) The binder joins the negative electrode current collector layer 2A to the negative electrode active material layer 2B, the negative electrode active material layer 2B to the solid electrolyte layer 3, and the various materials constituting the negative electrode active material layer 2B to each other. The binder can be the same material as that used for the positive electrode active material layer 1B. The binder content ratio can also be the same as that of the positive electrode active material layer 1B. If the binder is not needed, it does not need to be included.
[0051] Figure 2 shows an example in which the negative electrode 2 consists of a negative electrode current collector layer 2A and a negative electrode active material layer 2B, but the invention is not limited to this case. Figure 6 is an enlarged view of a feature portion of another example of an all-solid-state battery according to the first embodiment. The negative electrode 2D shown in Figure 6 has a negative electrode current collector 21 and a solid electrolyte 23. The negative electrode current collector 21 is, for example, an Ag alloy. The Ag alloy is, for example, an AgPd alloy or a Li-Ag alloy. The Ag alloy also functions as an active material. When the Ag alloy functions as the negative electrode active material, the all-solid-state battery has a high capacity and the energy density of the all-solid-state battery is improved.
[0052] "Manufacturing method for all-solid-state batteries" Next, the manufacturing method of the all-solid-state battery 10 will be described. First, the laminate 4 is manufactured. The laminate 4 is manufactured, for example, by a co-firing method or a sequential firing method.
[0053] The simultaneous firing method is a method of producing a laminate 4 by stacking the materials that form each layer and then firing them all at once. The sequential firing method is a method of firing each layer as it is formed. The simultaneous firing method can produce the laminate 4 with fewer steps than the sequential firing method. In addition, the laminate 4 produced by the simultaneous firing method is denser than the laminate 4 produced using the sequential firing method. The following explanation will use the simultaneous firing method as an example.
[0054] First, the materials constituting the laminate 4—the positive electrode current collector layer 1A, the positive electrode active material layer 1B, the solid electrolyte layer 3, the negative electrode active material layer 2B, and the negative electrode current collector layer 2A—are made into a paste. In the example shown in Figure 4, the positive electrode current collector 11 is coated with oxide 13 before being made into a paste. In the example shown in Figure 5, the materials constituting the intermediate layer 1F are also made into a paste.
[0055] The method for forming the paste from each material is not particularly limited; for example, a method of mixing the powders of each material with a vehicle to obtain a paste can be used. Here, "vehicle" is a general term for the medium in the liquid phase. The vehicle includes solvents and binders.
[0056] Next, a green sheet is prepared. The green sheet is obtained by applying a paste prepared for each material onto a substrate such as a PET (polyethylene terephthalate) film, drying it as needed, and then peeling off the substrate. The method of applying the paste is not particularly limited, and known methods such as screen printing, coating, transfer, and doctor blade can be used.
[0057] Next, the green sheets prepared for each material are stacked in the desired order and number of layers to create a laminated sheet. When stacking the green sheets, alignment and cutting are performed as needed. For example, when creating a parallel or series-parallel battery, the green sheets are stacked after alignment so that the end face of the positive electrode current collector layer 1A and the end face of the negative electrode current collector layer 2A do not coincide.
[0058] The laminated sheet may be manufactured by creating a positive electrode unit and a negative electrode unit and then laminating these units. The positive electrode unit is a laminated sheet in which a solid electrolyte layer 3, a positive electrode active material layer 1B, a positive electrode current collector layer 1A, and a positive electrode active material layer 1B are laminated in this order. In the example shown in Figure 5, an intermediate layer 1F is laminated between the positive electrode current collector layer 1A and the positive electrode active material layer 1B. The negative electrode unit is a laminated sheet in which a solid electrolyte layer 3, a negative electrode active material layer 2B, a negative electrode current collector layer 2A, and a negative electrode active material layer 2B are laminated in this order. The solid electrolyte layer 3 of the positive electrode unit and the negative electrode active material layer 2B of the negative electrode unit are laminated facing each other, or the positive electrode active material layer 1B of the positive electrode unit and the solid electrolyte layer 3 of the negative electrode unit are laminated facing each other.
[0059] Next, the fabricated laminated sheets are pressed together to improve the adhesion of each layer. Pressurization can be performed using, for example, a die press, hot water isostatic press (WIP), cold water isostatic press (CIP), or hydrostatic press. It is preferable to perform the pressurization while heating. The heating temperature during pressing should be, for example, 40°C to 95°C. Then, the pressed laminate is cut using a dicing device to form chips. Finally, the chips are subjected to a debinder treatment and firing to obtain a laminate 4 made of sintered material.
[0060] The debinding process can be carried out as a separate step from the firing process. Performing the debinding process allows the binder components contained in the chip to be thermally decomposed before the firing process, thereby suppressing the rapid decomposition of the binder components during the firing process. The debinding process can be carried out, for example, by heating in an atmospheric environment at a temperature of 300°C to 800°C for 0.1 hours to 10 hours. The atmosphere during the debinding process is an oxygen partial pressure environment in which the materials constituting the positive electrode, negative electrode, and solid electrolyte do not oxidize or are unlikely to oxidize, and the type of gas can be arbitrarily selected so that the materials constituting the positive electrode, negative electrode, and solid electrolyte do not react with the atmospheric gas. For example, it may be carried out in a nitrogen atmosphere, argon atmosphere, nitrogen-hydrogen mixed atmosphere, water vapor atmosphere, or an atmosphere of a mixture thereof.
[0061] The firing process is carried out, for example, by placing the chips on a ceramic base. The firing is carried out, for example, by heating to a temperature of 600°C to 1000°C in an atmospheric environment. The firing time is, for example, 0.1 hours to 3 hours. The atmosphere during the sintering process is an oxygen partial pressure environment in which the materials constituting the positive electrode, negative electrode, and solid electrolyte do not oxidize or are unlikely to oxidize, and the type of gas can be arbitrarily selected so that the materials constituting the positive electrode, negative electrode, and solid electrolyte do not react with the atmospheric gas. For example, it may be carried out in a nitrogen atmosphere, argon atmosphere, nitrogen-hydrogen mixed atmosphere, water vapor atmosphere, or an atmosphere of a mixture thereof.
[0062] Alternatively, the sintered laminate 4 (sintered body) may be placed in a cylindrical container with an abrasive such as alumina and barrel polished. This allows for chamfering of the corners of the laminate. Polishing may also be performed using sandblasting. Sandblasting is preferred because it allows for the removal of only specific parts.
[0063] Terminal electrodes 5 and 6 are formed on the opposing sides of the fabricated laminate 4. The terminal electrodes 5 and 6 can be formed using methods such as sputtering, dipping, screen printing, and spray coating, respectively. By going through the above steps, an all-solid-state battery 10 can be manufactured. If the terminal electrodes 5 and 6 are to be formed only in predetermined areas, the area is masked with tape or the like before the above process is performed.
[0064] The all-solid-state battery according to this embodiment has low internal resistance. This is thought to be because the compound represented by formula (1) used in the positive electrode active material 12 does not react easily with the solid electrolyte used in the solid electrolyte layer 3. For example, if the positive electrode active material 12 does not contain the compound represented by formula (1) and consists of LiMn2O4, intermediate products are formed between the solid electrolyte layer 3 and the positive electrode active material 12. These intermediate products are LiMn2O4 or Li2MnO3 containing excess Li, and are formed by the diffusion and reaction of Li in the solid electrolyte. These intermediate products and the Li-deficient solid electrolyte cause an increase in the internal resistance of the all-solid-state battery. In contrast, the compound represented by formula (1) used in the positive electrode active material 12 does not react easily with the solid electrolyte used in the solid electrolyte layer 3, and intermediate products are less likely to be formed.
[0065] Although embodiments of the present invention have been described in detail above with reference to the drawings, the configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications to the configurations are possible without departing from the spirit of the present invention. [Examples]
[0066] "Example 1" (Preparation of positive electrode paste) The positive electrode current collector layer paste is made using Ag, Pd, and LiNi 0.5 Mn 1.5 A powder was prepared by mixing O4 with other substances in a volume ratio of 40:10:50. Ethyl cellulose and dihydroterpineol were added to this powder and mixed. Ethyl cellulose acted as the binder, and dihydroterpineol acted as the solvent.
[0067] The positive electrode active material layer paste is LiNi 0.5 Mn 1.5 It was prepared by adding ethylcellulose and dihydroterpineol to O4 and mixing them.
[0068] (Preparation of solid electrolyte layer paste) Li2CO3, SiO2, and Li3PO4 were used as starting materials and mixed in a molar ratio of 2:1:1. The mixing was performed wet for 16 hours using a ball mill with water as the dispersion medium. The mixture was calcined at 950°C for 2 hours. 3.5 Si 0.5 P 0.5 O4 was prepared. Then, 100 parts by mass of this calcined powder, 100 parts by mass of ethanol, and 200 parts by mass of toluene were added to a ball mill and wet-mixed. Then, 16 parts by mass of polyvinyl butyral binder and 4.8 parts by mass of benzyl butyl phthalate were further added and mixed to prepare a solid electrolyte layer paste.
[0069] (Preparation of negative electrode paste) The negative electrode paste is made of Ag, Pd, and Li 3.5 Si 0.5 P 0.5 A powder was prepared by mixing O4 with other substances in a volume ratio of 40:10:50. Ethyl cellulose and dihydroterpineol were added to this powder and mixed.
[0070] (Fabrication of all-solid-state batteries) Next, the positive electrode unit and negative electrode unit were fabricated using the following procedure. First, a paste for the positive electrode active material was printed on the solid electrolyte layer sheet using screen printing to a thickness of 5 μm. Next, the printed paste for the positive electrode active material was dried at 80°C for 5 minutes. Then, a paste for the positive electrode current collector was printed on the dried paste for the positive electrode active material using screen printing to a thickness of 5 μm. Next, the printed paste for the positive electrode current collector was dried at 80°C for 5 minutes. Then, a paste for the positive electrode active material was printed again on the dried paste for the positive electrode current collector using screen printing to a thickness of 5 μm, and dried. After that, the PET film was peeled off. In this way, a positive electrode unit was obtained in which the positive electrode active material layer / positive electrode current collector layer / positive electrode active material layer were laminated in this order on the main surface of the solid electrolyte layer.
[0071] Next, a negative electrode paste was printed to a thickness of 10 μm onto the main surface of the solid electrolyte layer. Then, the printed negative electrode paste was dried at 80°C for 5 minutes.
[0072] The laminate was fabricated by creating a solid electrolyte unit by stacking five solid electrolyte layer sheets. Fifty electrode units (25 positive electrode units and 25 negative electrode units) were stacked alternately, sandwiching the solid electrolyte unit. At this time, the units were stacked with a staggered arrangement such that the current collector layer of odd-numbered electrode units extended only to one end face, and the current collector layer of even-numbered electrode units extended only to the opposite end face. Six solid electrolyte layer sheets were then stacked on top of these stacked units. After that, the laminate was formed by thermocompression bonding and then cut to create laminated chips. Subsequently, the laminated chips were co-fired to obtain the laminate. Co-fired firing was performed in an atmospheric environment by raising the temperature to 800°C at a heating rate of 200°C / hour, holding it at that temperature for 2 hours, and then allowing it to cool naturally.
[0073] A solid-state battery was fabricated by attaching terminal electrodes 5 and 6 to a sintered laminate (sintered body) using a known method. The resulting solid-state battery had the configuration shown in Figure 6. The volume ratio of each layer remained unchanged between the paste state before sintering and the state after sintering. Ag exists as elemental Ag and as a constituent element of AgPd alloys.
[0074] 100 similar samples were prepared, and their internal resistance was determined. The internal resistance was calculated as the average of these samples. The internal resistance was determined by dividing the voltage drop (V) from the pause to the start of discharge in the 10th cycle (after repeating the process 10 times) by the discharge current (A). One cycle consisted of constant current charging (CC charging) at a constant current of 100 μA until the battery voltage reached 3.9 V in a 60°C environment, followed by a 1-minute pause, and then discharge at a constant current of 100 μA until the battery voltage reached 0 V (CC discharge). Samples prepared under the same conditions were also disassembled, and the volume ratio (Va) of Ag and Ag alloy in the negative electrode current collector layer was determined.
[0075] Examples 2-5 Examples 2-5 use LiNi as the positive electrode active material. 0.5 Mn 1.5 The difference from Example 1 is that O4 and LiMn2O4 were used. Other conditions were the same as in Example 1, and the internal resistance and other parameters were determined. The volume ratio of powder used when preparing the paste for the positive electrode current collector layer and positive electrode active material layer in Examples 2 to 5 was as follows.
[0076] Example 2 Positive electrode current collector layer = Ag:Pd:LiNi 0.5 Mn 1.5 O4:LiMn2O4=40:10:40:10 Positive electrode active material layer = LiNi 0.5 Mn 1.5 O4:LiMn2O4 = 80:20
[0077] Example 3 Positive electrode current collector layer = Ag:Pd:LiNi 0.5 Mn 1.5 O4:LiMn2O4 = 40:10:30:20 Positive electrode active material layer = LiNi 0.5 Mn 1.5 O4:LiMn2O4 = 60:40
[0078] Example 4 Positive electrode current collector layer = Ag:Pd:LiNi 0.5 Mn 1.5O4:LiMn2O4=40:10:20:30 Positive electrode active material layer=LiNi 0.5 Mn 1.5 O4:LiMn2O4=40:60
[0079] Example 5 Positive electrode current collector layer=Ag:Pd:LiNi 0.5 Mn 1.5 O4:LiMn2O4=40:10:10:40 Positive electrode active material layer=LiNi 0.5 Mn 1.5 O4:LiMn2O4=20:80
[0080] "Examples 6 to 10" Each of Examples 6 to 10 differs from each of Examples 1 to 5 in that the solid electrolyte was changed from Li 3.5 Si 0.5 P 0.5 O4 to Li 3.5 Si 0.5 V 0.5 O4. For other conditions, the internal resistance and the like were determined in the same manner as in Example 1.
[0081] "Comparative Example 1" Comparative Example 1 differs from Example 1 in the following points. For Comparative Example 1 as well, the internal resistance and the like were determined in the same manner as in Example 1. Difference 1: For the production of the positive electrode current collector layer paste, a powder obtained by mixing Ag and Pd at a volume ratio of 80:20 was used. Difference 2: For the production of the positive electrode active material layer paste, LiMn2O4 was used instead of LiNi 0.5 Mn 1.5 O4. Difference 3: The negative electrode paste was formed into two layers, namely a negative electrode current collector layer paste and a negative electrode active material layer paste. For the negative electrode current collector layer paste, a powder obtained by mixing Ag and Pd at a volume ratio of 80:20 was used. The negative electrode active material layer paste was a mixture obtained by adding ethyl cellulose and dihydroterpineol to Li4Ti5O 12 (Li 4 / 3 Ti 5 / 3 O4).
[0082] "Comparative Example 2" Comparative Example 2 differs from Example 1 in that the positive electrode active material is LiMn2O4. In Comparative Example 2 as well, the internal resistance and the like were determined in the same manner as in Example 1.
[0083] The results of Examples 1 to 10 and Comparative Example 1 or 2 are summarized in Table 1 below. The symbol " / " in Table 1 represents the ratio at the time of preparation, and the abundance ratio after preparation is substantially the same as the ratio at the time of preparation.
[0084]
Table 1
[0085] When Example 1 and Comparative Example 1 were compared, Example 1 had a lower internal resistance than Comparative Example 1. It is considered that this is because the positive electrode active material and the solid electrolyte reacted in Comparative Example 1, resulting in the formation of an intermediate product.
[0086] "Examples 11 to 18" Examples 11 to 18 differ from Example 1 in that the composition ratio of the positive electrode active material was changed. For other conditions, the internal resistance and the like were determined in the same manner as in Example 1.
[0087] Example 11 differs from Example 1 in that LiNi is used as the positive electrode active material contained in the positive electrode active material layer. 0.1 Mn 1.9 O4 is used.
[0088] Example 12 differs from Example 1 in that LiNi is used as the positive electrode active material contained in the positive electrode active material layer. 0.9 Mn 1.1 O4 is used.
[0089] Example 13 differs from Example 1 in that LiNi is used as the positive electrode active material contained in the positive electrode current collector layer. 0.1 Mn 1.9 O4 is used.
[0090] Example 14 differs from Example 1 in that LiNi is used as the positive electrode active material contained in the positive electrode current collector layer. 0.9 Mn 1.1 O4 is used.
[0091] Example 15 uses LiNi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.1 Mn 1.9 The difference from Example 1 is that O4 was used.
[0092] Example 16 uses LiNi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.4 Mn 1.6 The difference from Example 1 is that O4 was used.
[0093] Example 17 uses LiNi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.6 Mn 1.4 The difference from Example 1 is that O4 was used.
[0094] Example 18 uses LiNi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.9 Mn 1.1 The difference from Example 1 is that O4 was used.
[0095] Examples 19-24 Examples 19-24 differ from Example 1 in that the positive electrode active material was changed. Other conditions were the same as in Example 1, and internal resistance and other parameters were determined accordingly.
[0096] Example 19 uses LiCo as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.1 Mn 1.9 The difference from Example 1 is that O4 was used.
[0097] Example 20 uses LiCo as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.5 Mn 1.5 The difference from Example 1 is that O4 was used.
[0098] Example 21 uses LiCo as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.9 Mn 1.1 The difference from Example 1 is that O4 was used.
[0099] Example 22 uses LiTi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.1 Mn 1.9 The difference from Example 1 is that O4 was used.
[0100] Example 23 uses LiTi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.5 Mn 1.5 The difference from Example 1 is that O4 was used.
[0101] Example 24 uses LiTi as the positive electrode active material in the positive electrode current collector layer and the positive electrode active material layer. 0.9 Mn 1.1 The difference from Example 1 is that O4 was used.
[0102] Example 25 Example 25 differs from Example 1 in that the positive electrode does not have a laminated structure of a positive electrode current collector layer and a positive electrode active material layer, but rather a single-layer structure of a positive electrode current collector layer. Other conditions were the same as in Example 1, and the internal resistance and other parameters were determined.
[0103] Examples 26-29 Examples 26-29 show Ag, Pd, and LiNi in the positive electrode current collector layer. 0.5 Mn 1.5 The difference from Example 1 is that the volume ratio of O4 was changed. Other conditions were the same as in Example 1, and the internal resistance and other parameters were determined.
[0104] In Example 26, the volume ratio of the positive electrode current collector layer was set to Ag:Pd = 80:20. That is, in Example 26, LiNi was used when preparing the negative electrode current collector layer paste. 0.5 Mn 1.5 O4 was not added. Example 27 uses Ag:Pd:LiNi as the volume ratio for the positive electrode current collector layer. 0.5 Mn 1.5 The ratio of O4 was set to 60:20:20. Example 28 uses a positive electrode current collector layer with a volume ratio of Ag:Pd:LiNi 0.5 Mn 1.5 O4 was set to 50:15:35. Example 29 uses Ag:Pd:LiNi as the volume ratio for the positive electrode current collector layer. 0.5Mn 1.5 The ratio of O4 was set to 30:8:62.
[0105] Examples 30-33 Examples 30-33 differ from Example 1 in that the composition ratio of the solid electrolyte contained in the solid electrolyte layer was changed. Other conditions were the same as in Example 1, and the internal resistance and other parameters were determined accordingly.
[0106] Example 30 uses Li as the solid electrolyte in the solid electrolyte layer. 3.1 Si 0.1 P 0.9 I set it to O4. Example 31 uses Li as the solid electrolyte in the solid electrolyte layer. 3.2 Si 0.2 P 0.8 I set it to O4. Example 32 uses Li as the solid electrolyte in the solid electrolyte layer. 3.4 Si 0.4 P 0.6 I set it to O4. Example 33 uses Li as the solid electrolyte in the solid electrolyte layer. 3.6 Si 0.6 P 0.4 I set it to O4.
[0107] Next, in Examples 34 to 41, a Li-Ag alloy was added to the negative electrode current collector layer, and similar investigations were conducted. However, the Li-Ag alloy was handled in a glove box with a dew point of -50°C, and the simultaneous firing was performed in an argon atmosphere, with the temperature raised to 800°C at a heating rate of 1200°C / hour, held at that temperature for 20 minutes, and then allowed to cool naturally.
[0108] "Example 34" Example 34 uses a Li-Ag alloy (Li) for a portion of the Ag in the negative electrode current collector layer. 3.1 The difference from Example 1 is that Ag was used. The amount of Li in the Li-Ag alloy was determined by quantitative analysis by X-ray diffraction (XRD). The negative electrode current collector layer consists of Li-Ag alloy, Ag, Pd, and Li 3.5 Si 0.5 P 0.5 The volume ratio of O4 to O4 was 2:38:10:50. The internal resistance of the all-solid-state battery was determined under the same conditions as in Example 1.
[0109] Example 35 Example 35 is a Li-Ag alloy (Li) in the negative electrode current collector layer. 3.1 Ag) to Li-Ag alloy (Li 4.7 The only difference from Example 34 is that Ag) was changed. Other conditions were the same as in Example 34, and the internal resistance of the all-solid-state battery was determined.
[0110] Examples 36 and 37 Examples 36 and 37 differ from Examples 34 and 35, respectively, in that Pd was not added when creating the negative electrode current collector layer. The volume ratio of the negative electrode current collector layer in Examples 36 and 37 was Li-Ag alloy:Ag:Li 3.5 Si 0.5 P 0.5 The ratio of O4 to 2:48:50 was set. The internal resistance of the all-solid-state battery was determined using the same conditions as in Example 34.
[0111] Examples 38-41 Examples 38-41 describe the composition of the solid electrolyte added to the solid electrolyte layer and the negative electrode current collector layer, with Li 3.5 Si 0.5 V 0.5 The use of O4 differs from each of Examples 34-37. Other conditions were the same as in Example 34, and the internal resistance of the all-solid-state battery was determined.
[0112] [Table 2]
[0113] [Table 3]
[0114] [Table 4] [Explanation of Symbols]
[0115] 1… Positive electrode, 1A, 1C, 1D, 1E… Positive electrode current collector layer, 1B… Positive electrode active material layer, 1F… Intermediate layer, 2, 2D… Negative electrode, 2A, 2C… Negative electrode current collector layer, 2B… Negative electrode active material layer, 3… Solid electrolyte layer, 4… Stacked layer, 5, 6… Terminal electrode, 10… All-solid-state battery, 11… Positive electrode current collector, 12… Positive electrode active material, 13… Oxide, 21… Negative electrode current collector, 22… Negative electrode active material, 23… Solid electrolyte
Claims
1. The sintered body comprises a positive electrode, a negative electrode, and a solid electrolyte layer between the positive electrode and the negative electrode. The positive electrode comprises one or more elements selected from Ag or Ag alloys and a compound having a spinel structure, and does not contain LiMn₂O₄. The solid electrolyte layer is γ-Li 3 PO 4 It contains a solid electrolyte having a crystal structure of the type, The compound having the spinel structure is Li α M β Mn 2-β O 4 ... (1) is expressed as, In formula (1) above, M is one or more atoms selected from transition metals, satisfying 0.8 ≤ α ≤ 1.2 and 0.1 ≤ β ≤ 0.9, an all-solid-state battery.
2. The aforementioned M is Ni, Said formula (1) is Li α Ni β Mn 2-β O 4 ... represented by (2), The all-solid-state battery according to claim 1, wherein in formula (2) above, 0.4 ≤ β ≤ 0.6 is satisfied.
3. The positive electrode comprises a first layer and a second layer, The first layer comprises the compound and one or more selected from Ag or Ag alloys. The all-solid-state battery according to claim 1, wherein the second layer is in contact with at least one main surface of the first layer.
4. The all-solid-state battery according to claim 3, wherein the total volume ratio of Ag and Ag alloy in the first layer is 40% or more and 85% or less.
5. The solid electrolyte contained in the solid electrolyte layer is Li 3+x Si x P 1-x O 4 The all-solid-state battery according to claim 1, including (0.2 ≤ x ≤ 0.6).
Citation Information
Patent Citations
Lithium ion secondary battery, and manufacturing method thereof
JP2011198692A
Lithium ion secondary battery
JP2016001597A
All-solid secondary cell
JP2016081791A
Total solid rechargeable battery
WO2007135790A1
Method for producing all-solid-state battery
WO2014050500A1